2016
DOI: 10.3109/00365521.2016.1166518
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in the treatment of hepatocellular carcinoma: a multi-centre real-world study

Abstract: Survival in patients with Child-Pugh C liver function or advanced functional impairment treated with sorafenib is poor and thus routine use of this agent in these patients does not appear justified, particularly given the high rate of adverse effects. AFP concentration on therapy may help identify favourable response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Multivariate analysis showed that indicators of liver function seemed to have a greater impact on prognosis than tumor burden, distribution, and tumor thrombus levels. It was confirmed by other researches that attention should be not only paid to tumorrelated conditions, but also to the liver function of patients (26,27).…”
Section: Discussionmentioning
confidence: 58%
“…Multivariate analysis showed that indicators of liver function seemed to have a greater impact on prognosis than tumor burden, distribution, and tumor thrombus levels. It was confirmed by other researches that attention should be not only paid to tumorrelated conditions, but also to the liver function of patients (26,27).…”
Section: Discussionmentioning
confidence: 58%
“…Diarrhea may be due to the blockage of EGFR, which is highly expressed in intestinal epithelium, and partly to the inflammatory reaction of the gut to sorafenib [46]. Few studies have reported a significant correlation between diarrhea and sorafenib efficacy; but from available data it seems that the occurrence of diarrhea is associated with improved OS [47,48] and longer TTP [49]. In our series, diarrhea occurred in 26.9% of patients and was mild in most cases.…”
Section: Validation Of the Scoring Systemmentioning
confidence: 58%
“…Sorafenib has been shown to improve survival in the treatment of HCC. However, only a limited number of patients have responded beneficially 3 . Prognosis of HCC remains poor, and HCC-related mortality is high 4 .…”
Section: Introductionmentioning
confidence: 99%